DETERMINAN PERTUMBUHAN EKONOMI DI KAWASAN TIMUR INDONESIA PADA TAHUN 2017–2024 - Jaya Putra, Alviansyah; Talakua, Jeane (Penerbit Lafadz Jaya, 2025)
The economic disparity between Western and Eastern Indonesia (KTI) remains a primary challenge in national development policy. Despite abundant natural resources, the eastern region faces significant obstacles in human capital development, investment attraction, price stability, and export competitiveness. A quantitative study examining 12 eastern provinces from 2017-2024 employed panel data regression analysis with Random Effect modeling. The study reveal that Foreign Direct Investment (FDI) and inflation have significantly negative impacts on economic growth. Conversely, the Human Development Index (HDI) and exports demonstrate moderately positive effects, while the Open Unemployment Rate shows negative but statistically insignificant influence. These results highlight the importance of enhancing human resource quality and strengthening export capacity, alongside the necessity for careful foreign investment monitoring and inflation control to achieve sustainable economic growth in eastern Indonesia. The study aims to provide evidence-based guidance for central and regional governments in formulating more contextual, equitable, and sustainable development policies.